Northern Connections: Interregional Contacts in Bronze Age Northern and Middle Sweden - Ojala, Karin; Ojala, Carl-Gösta (Open Archaeology, 2020)
Abstract This article examines northern connections in the Nordic Bronze Age, focusing on interregional contacts in middle and northern Sweden. In the article, we argue that it is important to incorporate a northern perspective in the discussions about the Scandinavian Bronze Age and its networks. We focus on the Mälaren Valley region, especially the province of Uppland, and the northern parts of Sweden, in particular the coastal areas of northern Sweden. We discuss some aspects of the archaeological material, which have been used in earlier discussions of interregional contacts in middle and northern Sweden during the Bronze Age, such as the Håga mound outside of Uppsala, and burial cairns and bronze artefacts in northern Sweden. Furthermore, we discuss eastern contacts with areas in present-day Finland and Russia, and how these have been interpreted in middle and northern Sweden. In our view, there is a need to critically examine interregional contacts and the construction of regional entities and borders in the Bronze Age. In order to better understand the relations between north and south, it is necessary to critically examine the research history behind the present-day conceptions of regions and borders, as well as the political dimensions and power relations involved.